THE EPIDEMIC ATTACK AGAINST WOMEN IN CYBER INFORMATION IN INDIA- A LEGAL DISSECTION - K. Sofiya; Valli, A.Vedha (International Journal of Psychosocial Rehabilitation, 2020)
Cyber violence is a great threat against the well being of an individual or group physically and mentally. Globally cyber violence is undoubtedly the new emerging form of violence and a most severe issue challenging women’s dignity, security and privacy. In country like India, it is a serious threat to women where cloud technology facilities are widespread but legal awareness is low. In India, according to NCRB report violence against women in online platform is increasing rapidly every single year. The main pitfall in cyber crime is the anonimity of the criminal. The main challenge in cyber crime is tracking the criminal and deciding the governing law since cyber space is boarderless. Most of the time these crimes goes unreported. This papers presents the different form of cloud based offence against women such as cyber stalking, cyber bullying, pornography etc. This paper also discuss about the International and National legal frameworks to tackle cyber violence against women and about the lack of implementation of laws.